Synergies and trade-offs among ecosystem services and biodiversity in different forest types inside and off-reserve in Tierra del Fuego, Argentina - Carrasco, Josela (2021)
Land use planning is mainly based on monetary values of provisioning ecosystem services (ES). However, many other non-monetary ES and biodiversity provide values for human well-being, and it should be included in the decisionmaking. The objective of this chapter was to characterize different ES (provisioning, cultural, supporting, regulating) and potential biodiversity in different forest types in Tierra del Fuego Province, Argentina. We map and extract information for provision of ES and biodiversity and compare them through univariate and multivariate methods. We found that each forest type showed different potential biodiversity that determines the need of specific conservation and management strategies. Forest types presented different types and levels of provision of the studied ES, where several synergies and trade-offs were observed according to the current economic activities. Beside this, ES and potential biodiversity of the forests are not equally represented in the currently protected natural reserve network, compared to the values at landscape level. These outputs can be used to improve the current land use planning and the effectiveness of conservation at landscape level.